Electromechanical Strain Responses of SEBS/Carbon Composite - Kim, Myeong Hee; Kim, Seong Hun; La Kwak, Hee; Park, Youn Duk; Hwang, Seung Sang; Koo, Chong Min; Hong, Soon Man (TAYLOR & FRANCIS LTD, 2010)
Electromechanical strain response of poly (styrene-b-ethylene-co-butylene-b-styrene) (SEBS)/carbon black(C) composite has been investigated by using laser displacement sensors. The composite consisting of neat SEBS, mineral oil and carbon powder was prepared by internal mixer. Compliant carbon paste electrodes were coated on both sides of the composite films. The SEBS and SEBS/C composite showed very fast electromechanical strain responses to the electric stimulation. The residual strain was rarely observed during the cyclic actuation tests. The SEBS/C composite with a small amount of carbon black had much higher electromechanical strain than the SEBS.
Keywords: ACTUATORS; ELASTOMERS